Stakeholders Engagement pada Publikasi CSR dan Asosiasinya dengan Kinerja Keuangan - Bakrie, Abdurrachman; Usman, Berto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to examine the impact of stakeholder reactions observed on social media platforms (Facebook, Twitter, Instagram, and Youtube) on financial performance. What distinguishes this study from previous research is the utilization of different variables and measurement methods. Previous researchers conducted their investigations on individual social media platforms, such as Facebook or Twitter. Meanwhile, in this study, we consider the stakeholder reactions extracted from Twitter, Instagram, Youtube platforms as well as employing control variables such as Size and Age. The hypotheses of this study are grounded in stakeholder theory and legitimacy theory. Purposive sampling was employed to collect data from companies listed on the Indonesia Stock Exchange from 2019 to 2022. Multiple linear regression was utilized as the analytical method, and the data were of a secondary nature, gathered through documentation methods. The research findings indicate that stakeholder reactions observed on Facebook, Twitter, and Instagram do not have a significant impact on financial performance, while when observed on Youtube, they exhibit a partial influence with a positive simultaneous effect. Keywords: Stakeholders, Financial Performance, ROA, ROE, Indonesia Stock Exchange, Social Media.